Measurement and analysis of toxic volatile organic compounds (VOC) and polycyclic aromatic hydrocarbons (PAH) at Singapore's integrated transport hubs (ITH) - Lee, Jeff Suk Hyun (Nanyang Technological University, 2021)
Millions of commuters should spend time waiting for their buses at bus interchanges every day in Singapore. Environmental exposure to vehicular emissions at transport hub and associated risks are of public concern. To date, limited studies have focused on the indoor air quality at Integrated Transport Hubs (ITHs), which are fully air-conditioned bus interchanges adjoined with subway stations and commercial facilities. In this study, 12 representative Volatile Organic Compounds (VOCs) and 16 EPA priority pollutant Polycyclic Aromatic Hydrocarbons (PAHs) were selected, collected from 9 bus interchanges at both indoor waiting area and bus park sampling points, and then analyzed. The daily VOCs and PAHs exposure for commuters were estimated by considering inhalation and dermal doses using Monte Carlo simulation (n=100,000), and human health risks for the exposure to selective pollutants were further evaluated. The median concentration of total VOCs (TVOCs), total gaseous PAHs (TgPAHs) and total particulate-bound PAHs (TpPAHs) in indoor areas were 30.42 μg/m3, 18.99 ng/m3 and 1.38 ng/m3, respectively. Besides, the median concentrations for bus parks were 20.24 μg/m3, 24.26 ng/m3 and 1.94 ng/m3 in sequence. In general, the pollutant concentration levels were not significantly different between waiting areas and bus parks, but showed positive correlations (TVOCs: r = 0.90 , p < 0.001; TgPAHs: r = 0.75, p < 0.001; TpPAHs: r = 0.39, p < 0.05), suggesting some air exchange dependency between the spaces. The high correlations between VOCs and gPAHs components were found, which implied the bus exhaust might be the dominant source of the pollutants. The indoor waiting area to bus park pollutant concentration ratio (I/B ratio), a new indicator representing the concentration relationship between indoor and bus park samples, was calculated for each pollutant group, and lower I/B ratios of pollutants were found (TVOCs: 0.98; TgPAHs: 0.76; TpPAHs: 0.71) in the bus interchanges with fully sheltered bus parks than those with open/partially enclosed bus parks (TVOCs: 1.28; TgPAHs: 1.31; TpPAHs: 0.90). The findings in this study imply that the fully sheltered bus park may affect the dilution of air pollutants resulting in the accumulation in adjacent indoors. From the result of the dose estimation, it was found that inhalation was the dominant exposure route of VOCs accounted for 99%, while dermal absorption was the major route of PAHs accounted for 82%. Most concentration levels of VOCs at Singapore's ITHs were found to be below EPA's reference concentrations (RfC) except for naphthalene, but the maximum concentration was less than the twice of its safety benchmark. However, benzene, ethylbenzene, styrene and naphthalene exceed the stringent OEHHA benchmarks, as similar to other countries' reports. The concentration levels of PAHs at ITHs were found to be within their safety benchmarks through the estimation of Incremental Lifetime Cancer Risk (ILCR) for carcinogenic risk and the comparison with EPA’s RfC for noncarcinogenic risk.